Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.drugalcdep.2017.01.014
|View full text |Cite
|
Sign up to set email alerts
|

A pilot investigation of acute inhibitory control training in cocaine users

Abstract: Background Disrupted response inhibition and presence of drug-cue attentional bias in cocaine-using individuals have predicted poor treatment outcomes. Inhibitory control training could help improve treatment outcomes by strengthening cognitive control. This pilot study assessed the effects of acute inhibitory control training to drug- and non-drug-related cues on response inhibition performance and cocaine-cue attentional bias in cocaine-using individuals. Methods Participants who met criteria for a cocaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…For example, Rush and colleagues (2020) found that inhibitory control training by participants with cocaine use disorder improved stop-signal task performance but did not affect delay discounting performance. Similarly, Alcorn and colleagues (2017) found in a similar participant population that inhibitory control training improved stop-signal task performance but did not affect attentional bias for cocaine cues. Although more systematic examinations of far-transfer to the untrained domains of impulsivity would be beneficial, these results are consistent with a broader cognitive science literature for which meta-analyses on cognitive training have shown short-term improvements in near-transfer tasks but small or no effects in generalization of far-transfer to other cognitive skills in the short and long-term (e.g., inhibitory processes in attention short-term effects d = 0.32, long term effects d = 0.09; Melby-Lervåg & Hulme, 2013).…”
Section: Empirical Arguments For Rejecting Impulsivity As a Psycholog...mentioning
confidence: 72%
See 1 more Smart Citation
“…For example, Rush and colleagues (2020) found that inhibitory control training by participants with cocaine use disorder improved stop-signal task performance but did not affect delay discounting performance. Similarly, Alcorn and colleagues (2017) found in a similar participant population that inhibitory control training improved stop-signal task performance but did not affect attentional bias for cocaine cues. Although more systematic examinations of far-transfer to the untrained domains of impulsivity would be beneficial, these results are consistent with a broader cognitive science literature for which meta-analyses on cognitive training have shown short-term improvements in near-transfer tasks but small or no effects in generalization of far-transfer to other cognitive skills in the short and long-term (e.g., inhibitory processes in attention short-term effects d = 0.32, long term effects d = 0.09; Melby-Lervåg & Hulme, 2013).…”
Section: Empirical Arguments For Rejecting Impulsivity As a Psycholog...mentioning
confidence: 72%
“…Inhibitory control training targets motor impulsivity by training participants to decrease prepotent responses to cues relevant to negative health behaviors (e.g., drugs, unhealthy foods). These inhibitory training procedures have resulted in improvements in the trained or similar tasks (i.e., near-transfer; improvements in response inhibition following inhibitory control training; Alcorn, Pike, Stoops, Lile, & Rush, 2017; Houben, Nederkoorn, Wiers, & Jansen, 2011; Rush, Strickland, Pike, Studts, & Stoops, 2020; Strickland, Hill, Stoops, & Rush, 2019). However, far-transfer involving improvements in other cognitive domains relevant to impulsivity appear poor.…”
Section: Empirical Arguments For Rejecting Impulsivity As a Psycholog...mentioning
confidence: 99%
“…However, negative or mixed outcomes have also been reported (Bowley et al, 2013, Smith et al, 2017, Wanmaker et al, 2018. Although fewer studies have addressed other substance use disorders, existing research indicates similar improvements in near-transfer performance (Alcorn et al, 2017, Bickel et al, 2011, but is varied with respect to changes in far-transfer performance or substance use (e.g., Adams et al, 2017, Rass et al, 2015, Schulte et al, 2018, for general meta-analysis on working memory effects see Melby-Lervag and Hulme, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to some studies using formal training of working memory (e.g., [83]) to evaluate their direct impact on unhealthy behaviors (e.g., alcohol abuse), which can be positive in nonclinical samples [84], but not clinical population [85], modified versions of response inhibition tasks have served as training paradigms [79,[86][87][88][89][90].…”
Section: Restoring Inhibitory Controlmentioning
confidence: 99%